Characteristics and outcome of suspected cerebrovascular disease in dogs: 66 cases (2009‐2016). (29th September 2021) - Ozawa, T.; Miura, N.; Hasegawa, H.; Uemura, T.; Nakamoto, Y.; Tsujio, M.; Takeuchi, T.; Shiraishi, M.
Abstract : Objectives: To characterise the clinical signs of suspected cerebrovascular disease in dogs. Materials and Methods: Medical records of one hospital were searched from November 2009 to December 2016 for dogs that suffered of cerebrovascular disease. We diagnosed cerebrovascular disease based on acute onset, clinical signs and magnetic resonance imaging findings. The medical history, clinical signs, concurrent disease, area of infarction, cerebrospinal fluid results, month at onset and outcome were investigated in the cerebrovascular disease group and in a control group (dogs with brain disorders other than cerebrovascular disease). Results: A total of 122 CVD cases were extracted from the 5312 patients that visited during the study period. Of these 122 cases, 66 (1.2%) matched the subject selection criteria of our study and were included in the analysis. Forebrain infarction was observed in 51 of 66 cases, of which 24 (47.1%) suffered from seizures. The number of dogs diagnosed with cerebrovascular disease was disproportionately high in August (nine of 59 cases) and December (13 of 59 cases). In the outcome survey, deterioration was observed in 11 of 55 cases. Clinical Significance: Seizure is an important clinical sign of cerebrovascular disease in dogs. There was a significant seasonal variation in the number of dogs diagnosed with cerebrovascular disease in Japan. Clinical features observed in this report differ from those of previous reports and highlight the need for additional research in this area.